Children's Acquisition of Homogeneity in Plural Definite Descriptions - Tieu, Lyn; Križ, Manuel; Chemla, Emmanuel (Frontiers in Psychology, 2019)
Plural definite descriptions give rise to homogeneity effects: the positive "The trucks are blue" and the negative "The trucks aren't blue" are both neither true nor false when some of the trucks are blue and some are not, that is, when the group of trucks is not homogeneous with respect to the property of being blue (Löbner 1987, 2000; Schwarzschild 1994; Križ 2015c). The only existing acquisition studies related to the phenomenon have examined children's comprehension only of the affirmative versions of such sentences, and moreover have yielded conflicting data; while one study reports that preschoolers interpret definite plurals maximally (Munn et al. 2006, see also Royle et al. 2018), two other studies report that preschoolers allow non-maximal interpretations of definite plurals where adults do not (Karmiloff-Smith 1979; Caponigro et al. 2012). Moreover, there is no agreed upon developmental trajectory to adult homogeneity. In this paper, we turn to acquisition data to investigate the predictions of a recent analysis of homogeneity that treats homogeneous meanings as the result of a scalar implicature (Magri 2014). We conducted two experiments targeting 4- and 5-year-old French-speaking children's interpretations of plural definite descriptions in positive and negative sentences, and tested the same children on standard cases of scalar implicature. The experiments revealed three distinct subgroups of children: those who interpreted the plural definite descriptions existentially and failed to compute implicatures; those who both accessed homogeneous interpretations and computed implicatures; and finally, a smaller subgroup of children who appeared to access homogeneous interpretations without computing implicatures. We discuss the implications of our findings, which appear to speak against the implicature theory as the adult-like means of generating homogeneous meanings.